Pengaruh Positioning Dan Lokasi Terhadap Keputusan Pembelian (Survei Pada Konsumen Kedai Caffee Wartel) - Pira Aprilianti; Arga Sutrisna; Suci Putri Lestari (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to examine and analyze the effect of positioning and location on purchasing decisions at cafe shops. This study used a sample of 100 respondents from cafe shop consumers. In this study using primary data obtained from distributing questionnaires. The analytical method used in this research is multiple linear analysis. The results of the study show that positioning and location have a positive and significant simultaneous effect on purchasing decisions with an R-Square value of 68%. This shows that when the location and positioning partially effect are good and supportive, it will be able to increase the number of sales.